2009
DOI: 10.1007/s10409-009-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Modal identification based on Hilbert-Huang Transform of structural response with SVD preprocessing

Abstract: In recent years, Empirical mode decomposition and Hilbert spectral analysis have been combined to identify system parameters. Singular-Value Decomposition is proposed as a signal preprocessing technique of Hilbert-Huang Transform to extract modal parameters for closely spaced modes and low-energy components. The proposed method is applied to a simulated airplane model built in Automatic Dynamic Analysis of Mechanical Systems software. The results demonstrate that the identified modal parameters are in good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The advantages of ambient vibration monitoring in the field of structural engineering have been well documented in the literature [18][19][20][21][22][23][24][25]. Recently, research in signal processing witnessed the development of new and powerful classes of methods: BSS [26][27][28][29], and timefrequency methods such as empirical modal decomposition (EMD) [30,31] and wavelet-transforms [32] to name a few. Although these methods in themselves show excellent capabilities in dealing with ambient modal identification, their direct use to solve the problem at hand remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of ambient vibration monitoring in the field of structural engineering have been well documented in the literature [18][19][20][21][22][23][24][25]. Recently, research in signal processing witnessed the development of new and powerful classes of methods: BSS [26][27][28][29], and timefrequency methods such as empirical modal decomposition (EMD) [30,31] and wavelet-transforms [32] to name a few. Although these methods in themselves show excellent capabilities in dealing with ambient modal identification, their direct use to solve the problem at hand remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Some HHT applications in engineering and other areas have been presented by Huang and Shen (2005) and Huang and Attoh-Okine (2005). More research about the EMD applications in signal processing can be found in Chen and Feng (2003), Yang et al (2003aYang et al ( , 2003b, Yang et al (2004), Peng et al (2005), Shi and Law (2007), Shi et al (2009), and Zheng et al (2009). To solve the modal-mixing problem, Wu and Huang (2009) further developed ensemble EMD to decompose the signal.…”
Section: Hilbert Transform and Applications In Civil Engineering Strumentioning
confidence: 99%
“…It is seen from Table 1 that the detection quality of damping ratios based on the HHT approach is much better than that using the bandwidth method. Zheng et al [36] developed an improved approach by using the singular-value decomposition as a signal preprocessing technique of HHT to extract modal parameters for closely spaced modes and low-energy components. The proposed method is applied to a simulated airplane model and the results demonstrate the validity of the approach.…”
Section: Structures With Closely Spaced Modal Frequenciesmentioning
confidence: 99%